Energy policy influence on the surplus welfare of subscribers in present of cleaner energy sources. (20th January 2021) - Wang, Hui; Guo, Yanlong; Guo, Haohui; Safar, Benjamin
Abstract: Nowadays, due to the greenhouse gas emissions as well as climate variation and weather warming, the power generation is one of the most important issues for reviewing the regulations, applying the restrictions, and offering various solutions to solve the mentioned problems. One of the proposed solutions is the applying of Energy Policies (EPs) aimed at promoting renewable energy sources. The effectiveness of these policies in increasing the penetration rate of renewable energy sources is obvious. However, the effects of these policies on the total social welfare are not assessed till now. The overall welfare includes the profits of the production company of the renewable energy sources and the surplus welfare of subscribers. In this paper, the results of the implementation of a well–known policy as quota obligation with tradable Green Certificates (GCs) and its effect on the surplus welfare are studied, based on the product development planning. To obtain the paper aims, the desired EP is combined with the problem of product development planning, and a comprehensive model for development planning is presented from the perspective of a production company. The model is implemented in the form of a Mixed Integer Non–Linear Problem (MINLP) in the GAMS optimization software using the BARON optimizer. Also, for solving the problem, two different scenarios as without policy of quota obligation and with it, are considered. The social welfare is evaluated by the Virtual Price Index (VPI). The results show that the surplus welfare of the subscribers increase in the long term horizon, while it was lower than the profit of the production company at short term analysis. Besides, with applying the policy of quota obligation with tradable GCs, not only the penetration of the renewable energy sources increased (more than 60%), but also the surplus welfare increased more than 10 7 . In the second scenario, the price of production is decreased and the number of cleaner sources is increased. Editor highlights: Applying the Energy policy into cleaner production development planning. Analysis of surplus welfare in two scenarios, with and without of the desired EP. Using of MINLP, to solve the problem by consideration of different constraints. Propose index to study the net profit of production company in various years. The results show increment of cleaner sources promotion, profit and social welfare.